Perancangan Football Training Camp PSMS Medan dengan Tema Arsitektur Post Modern - Hanafi, Hanafi; Barky, Neneng Yulia (Universitas Medan Area, 2024)
A province on the island of Sumatra, specifically in the city of Medan,there is a very legendary club called the Medan Surrounding Football Association or what is often called PSMS Medan. PSMS Medan once achieved achievements and its glory days in the 1970s to 1980s, but after that PSMS Medan’s achievements declined until now and play league 2. The reason PSMS achievements have decreased is due to lack of facilities and lack of coaching, including the lack of field facilities for training. By planning a football training camp it can charge the views of the people of North Sumatra, especially the city of Medan.towards PSMS Medan due to its declining achievements in recent years. By designing a quality football training ground to improve the quality of PSMS Medan players. The design process uses post modern architectural principles with the robert ventury appoach applied to the shape of the building and the appearance of the building. The author chose robert ventury’s post modern architectural appoach in designing the Football Training Camp so that the shape of the buildings arround the site directly reflects the function of the building.